Effects of hydroalcoholic extract of Solidago chilensis Meyen on nociception and hypernociception in rodents - Elena L. A. Malpezzi-Marinho; Graziela R. Molska; Lyvia I. G. P. Freire; Cristiane I. Silva; Eduardo K. Tamura; Laís F. Berro; Carlos A. Parada; Eduardo Ary Villela Marinho (BMC, 2019)
Abstract Background Solidago chilensis (syn. microglossa) is a plant from the Asteraceae family widely distributed in South America and used to treat inflammatory diseases. In 2009, it was listed as one of the native medicinal herbal plants used in the Brazilian public health system. In addition to its anti-inflammatory properties, a recent clinical study has shown antinociceptive effects of S. chilensis, introducing a new potential medical use for this plant. The aim of the present study was to investigate the antinociceptive activity of the hydroalcoholic extract of Solidago chilensis (HESc) in rodent models of pain. Methods The dried plant extract was obtained from its aerial parts, maintained in ethanol (100 g/l) and filtered. Rats or mice were treated with intraperitoneal injections of HESc (3, 10 or 30 mg/kg) 30 min before being submitted to writhing, 0.2%-formaline or hot-plate tests or prostaglandin E2 (PGE2) administration in the hind paw. Mechanical hypernociception and motor impairment were evaluated by electronic von Frey and rota-rod, respectively. Results HESc dose-dependently inhibited abdominal contortions in the writhing test and attenuated phases I and II formalin-induced nociceptive behavior. Treatment with HESc also increased thermal threshold and decreased PGE2-induced hypernociception without promoting motor impairment. Conclusions Our data suggest that, when systemically administered, HESc decreases nociception without inducing a sedative effect. Importantly, this effect was observed in both inflammatory and non-inflammatory models of pain and nociception, suggesting a specific non-inflammatory mechanism of HESc on pain. Our findings indicate that S. chilensis might be an important adjuvant in pain management.